Function and shift of Meaning of Ma’meugang Tradition in Aceh Society in Welcoming Islamic Holy Days: Fungsi dan Pergeseran Makna Tradisi Ma'meugang Pada Masyarakat Aceh Dalam Menyambut Hari Besar Islam - Avicenna Al Maududdy; Fatianda, Septian (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2024)
Abstract The people of Aceh have carried out the Ma'meugang or meugang tradition since the Sultanate era until now. Approaching the three holidays of Id Fitr, Id Adha, and Ramadhan are the times when parties are held. Meugang Day has cultural and religious values ​​besides eating meat. This article will discuss how the history of ma'meugang day in Acehnese society?. How is the function and meaning of the ma'meugang tradition in Acehnese society?. Why has there been a shift in the function and meaning of the ma'meugang tradition in Acehnese society?. This qualitative research collects sources through literature study and field research. The research results show that Meugang day celebrations in Aceh incorporate Islamic values. When viewed from a cultural perspective, meugang is just a tradition that has no connection with religion, but when viewed in its context and background, it becomes part of the practice of the Islamic religion. Keywords : Ma'meugang, Tradition, Islam, Aceh Abstrak Masyarakat Aceh telah melakukan tradisi Ma'meugang atau meugang sejak zaman Kesultanan hingga saat ini. Menjelang bulan puasa, Id Fitri, dan Id Adha adalah waktu di mana pesta diadakan. Hari Meugang memiliki nilai budaya dan religius selain makan daging. Artikel ini akan membahas bagaimana sejarah hari ma’meugang dalam masyarakat Aceh?. Bagaimana fungsi dan makna tradisi Ma’meugang dalam masyarakat Aceh?. Mengapa terjadi pergeseran fungsi dan makna tradisi ma’meugang dalam masyarakat Aceh?. Penelitian kualitatif ini mengumpulkan sumber melalui penelitian kepustakaan dan lapangan. Hasilnya menunjukkan bahwa perayaan hari meugang di Aceh menggabungkan nilai-nilai Islam. Jika dilihat dari Dari sudut pandang budaya, meugang hanyalah sebuah tradisi tanpa terkait agama, tapi ketika dilihat dalam konteks dan sejarahnya itu menjadi bagian dari pengamalan agama Islam. Kata Kunci : Ma'meugang, Tradisi, Islam, Aceh